A longitudinal perspective on inductive reasoning tasks. Illuminating the probability of change - Ifenthaler, Dirk; Seel, N. (Pergamon, 2011)
Cognitive scientists have studied internal cognitive structures, processes, and systems for decades in order to understand how they function in human learning. Nevertheless, questions concerning the diagnosis of changes in these cognitive structures while solving inductive reasoning tasks are still being scrutinized. This paper reports findings from an experimental study in which 64 participants in three experimental groups solved tasks at ten measurement points. We were able to illuminate changes of cognitive structures and found significant differences between the treatments. The results also indicate that supportive information is an important aid for developing cognitive structures while solving inductive reasoning tasks. © 2010 Elsevier Ltd.